PROBLEM PRACOWNICZEGO PODPORZĄDKOWANIA KADRY KIEROWNICZEJ NAJWYŻSZEGO SZCZEBLA W ORGANIZACJACH GOSPODARCZYCH – ARTYKUŁ DYSKUSYJNY - Duraj, Tomasz (Zeszyty Prawnicze, 2017)
The Problem of Employment Subordination of Senior Management in Economic Organizations Summary The subject of this study is to show the doubts and controversies that appear in the doctrine of labor law and judicial decisions in the interpretation of employment subordination of senior management in economic organizations. Taking into consideration the specificity of functions performed by senior management, the employment relationship of these employees is so much different from the typical standards that in the literature on the subject there has developed a view that there exists, in the case of the discussed category of senior managers, a not typical or even atypical employment relationship. This untypical nature is the reason why some institutions or requirements regulated in the labor law are not applicable to this group of managers, or lose their usefulness or even sense, as inadequate in view of the specific character of the managerial function. In relation to this issue, the most interesting appears the problem of interpretation of the employment subordination of senior management, taking into consideration the fact, that those employees, being on the top of the management hierarchy in a given organization, work in the condition of relative independence, being characterized by the absence of a superior and considerable freedom in the area of organizing own work in terms of time and place. The author of the article is critical of the multitude of the approaches to understanding the employment subordination of senior management. It must be remembered, that subordination is considered the most important (constitutive) feature of employment relationship, differentiating it from other employment relations (especially those of civil law character), and at the same time indicates the scope of use of employment relationship, also with regard to managers. This situation leads to blurring the differences, which are already vague, between labor law and civil law forms of employing managing personnel, creating a state of uncertainty about a lawful choice of one of the mentioned here in basis of employing senior managing personnel.